2019
DOI: 10.3390/v11020147
|View full text |Cite
|
Sign up to set email alerts
|

Detection of RNA-Dependent RNA Polymerase of Hubei Reo-Like Virus 7 by Next-Generation Sequencing in Aedes aegypti and Culex quinquefasciatus Mosquitoes from Brazil

Abstract: Advancements in next-generation sequencing and bioinformatics have expanded our knowledge of the diversity of viruses (pathogens and non-pathogens) harbored by mosquitoes. Hubei reo-like virus 7 (HRLV 7) was recently detected by the virome analysis of fecal samples from migratory birds in Australia. We now report the detection of RNA-dependent RNA polymerase sequences of HRLV 7 in pools of Aedes aegypti and Culex quinquefasciatus mosquitoes species from the Brazilian Amazon forest. Phylogenetic inferences indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…In agreement with previous virome studies, most of the taxa derived from honey-baited FTA cards have been identified in various invertebrates [39] and associated to mosquitoes [40]. Additionally, mosquito-specific viruses detected in FTA cards (Table 2) have been described as part of the viral communities harbored by several mosquito species in different geographic regions [41][42][43][44][45][46][47][48]. Bold type corresponds to the selected viruses for primers design.…”
Section: Virome Composition On Honey-baited Fta Cards During Entomolosupporting
confidence: 86%
“…In agreement with previous virome studies, most of the taxa derived from honey-baited FTA cards have been identified in various invertebrates [39] and associated to mosquitoes [40]. Additionally, mosquito-specific viruses detected in FTA cards (Table 2) have been described as part of the viral communities harbored by several mosquito species in different geographic regions [41][42][43][44][45][46][47][48]. Bold type corresponds to the selected viruses for primers design.…”
Section: Virome Composition On Honey-baited Fta Cards During Entomolosupporting
confidence: 86%
“…For example, the Amazon region is identified as the starting point for transmission of the yellow fever virus in a recent outbreak in Brazil that killed almost 700 people between December 2016 and March 2018 and the Amazon rainforest functions as a 'reservoir' region for several arboviruses [42]. Other studies have been identified novel virus presents in the mosquito microbiota in this region, in the host Aedes aegypti and anophelines [17,18,43], reinforcing the idea that our current knowledge about the diversity of viruses is still very limited. Furthermore, insect-specific virus (ISV) compose the majority of mosquito virome the virus-virus interactions may affect the transmission of some viral pathogens [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies from our group have described unusual viral sequences from Flaviridae and Reoviridae families in Ae. aegypti mosquitoes in the Amazon [17,18]. Using an NGS metagenomic approach, this study aimed to identify novel viruses in Ae.…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory workflows can substantially affect the ability of metatranscriptomic sequencing to detect arboviruses in a mosquito pool. A popular way to increase sensitivity is by enriching for arbovirus using size filtration 16 , PEG precipitation 17 or sequence-independent amplification 12 . While this does increase the number of viral sequences, enrichment can also introduce bias 18,19 .…”
Section: Sensitivity and Specificity Of Metatranscriptomics As An Arbmentioning
confidence: 99%